Aggregation and Rheological Behavior of the Lavender Oil-Pluronic P123 Microemulsions in Water-Ethanol Mixed Solvents - Chat, Oyais Ahmad (Langmuir : the ACS journal of surfaces and colloids, 2018)
The effect of lavender oil on aggregation characteristics of P123 in aqueous-ethanolic solutions is investigated systematically by DLS, SANS, and rheology. The solubilization capacity of the P123 based formulations toward Lavender oil increased by increasing P123 concentration. The study unveiled the importance of the short chain alcohol-ethanol, as solubilization enhancer. The apparent hydrodynamic radius (Rh) increased significantly with an increase in lavender oil concentration up to maximum oil solubilization capacity of the copolymer at a particular ethanol concentration. DLS measurements on 5, 10, and 15 wt% P123 in the presence of 25% ethanol revealed the presence of large-sized micellar clusters in addition to the oil swollen micelles. The core size (RC), radius of hard sphere (RHS), and aggregation number (N) obtained from SANS profiles showed considerable enhancement with the addition of lavender oil confirming penetration of oil inside the copolymer. Rheological studies showed that viscosity also increased significantly with the addition of lavender oil near the maximum loading limit of the P123 concentration. Quite interestingly, the sol-gel transition temperature displayed a strong dependence on both P123 as well as oil concentration and decreased almost linearly by increasing oil concentration. This study demonstrates the use of a biocompatible and temperature sensitive self-assembled P123 based formulation for lavender oil solubilization that can be beneficial in the cosmetic industry wherein controlled release of fragrances and so forth is demanded